Spatial distribution of subtidal meiobenthos along estuarine gradients in two Southern European estuaries (Portugal). - Alves, Ana (2012)
Abstract The spatial variation in abundance and composition of subtidal meiobenthos communities was studied in two Portuguese estuaries under distinct degrees of anthropogenic pressure. Samples were collected from 20 sampling stations along both estuarine gradients from freshwater (<0.5) to euhaline areas (>30). Of these stations 11 were located in the Mondego estuary, a system exposed to high anthropogenic stress, and 9 in the Mira estuary, a naturally stressed system located inside the Natural Park ‘Costa Vicentina’ (south-western coast of Portugal). Total meiobenthos density was higher in the Mira estuary and in both estuaries the community was dominated by nematodes. Among the twelve taxa identified in the Mira estuary, Harpacticoid copepods and Polychaeta were the second and the third most abundant groups respectively. In the Mondego estuary, Polychaeta was the second while Harpacticoid copepods was the third most abundant group in the thirteen total taxa recorded. Estuarine gradients of salinity, particles size and water nutrients were clearly detected in both estuaries and there was significant spatial heterogeneity in abundance and composition of the subtidal meiobenthos communities along these environmental gradients. Accordingly, three distinct sections were identified in both estuaries: (i) freshwater sections, where total density, and density of nematodes and Harpacticoid copepods reached minimum values; (ii) oligohaline and mesohaline sections, where the total density was low and diversity was poor; and (iii) polyhaline and euhaline sections, where both total density and diversity reached the highest values. The similar spatial distribution of meiobenthos assemblages in both estuaries suggests that natural stressors may be the major factors controlling the physicochemical conditions that determine meiobenthos community patterns. The mesoscale variability of subtidal meiobenthos density and composition within estuaries (in the order of kilometres) seems to be more important than the variability between estuaries (at the scale of hundreds of kilometres), a common feature in intertidal systems. From the management point of view, these results, based on higher taxa resolution, represent an obvious constraint to the applicability of ecological quality evaluation tools.